(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
The article presents the new publication dedicated to a Croatian Glagolitic manuscript, known as the Second Beram Breviary, or the Second Ljubljana Breviary, given that it is kept in the National and University Library in Ljubljana (pressmark Ms 163). This new edition Studije o Drugome beramskom brevijaru (eds. M. Mihaljević, A. Radošević, Bibliotheca glagolitica croatica, knj. 4, Znanstveni centar izvrsnosti za hrvatsko glagoljaštvo, Staroslavenski institut, Zagreb, 2021) represents a continuation to the previously published four volumes: the facsimile edition and the transliterated text of the first part (264 sheets) and the second part of the Breviary (176 sheets). The book contains a detailed palaeographic description, textual, literary-historical, liturgical and linguistic analysis of the manuscript. Keywords: Croatian Glagolitic manuscript; Second Beram Breviary.